2010
DOI: 10.1007/s00294-010-0313-3
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of the C-terminal FATC domain of Saccharomyces cerevisiae Tra1

Abstract: Tra1 is a component of the Saccharomyces cerevisiae SAGA and NuA4 complexes and a member of the PIKK family, which contain a C-terminal phosphatidylinositol 3-kinase-like (PI3K) domain followed by a 35-residue FATC domain. Single residue changes of L3733A and F3744A, within the FATC domain, resulted in transcriptional changes and phenotypes that were similar but not identical to those caused by mutations in the PI3K domain or deletions of other SAGA or NuA4 components. The distinct nature of the FATC mutations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(67 citation statements)
references
References 85 publications
(124 reference statements)
7
60
0
Order By: Relevance
“…A single deletion at the junction of the PI3K C-terminal lobe and FATC domain gave rise to viable yeast, whereas a complete deletion of the FATC domain was inviable, possibly due to poor protein stability, since this deletion resulted in a truncation in the C terminus (see below). This is consistent with a previous study suggesting that the FATC domain is important for integrity of complexes containing members of the PIKK protein family (36,41). We also found that Tra1 regions spanning HEAT repeats 8 and 9, 10 to 25, 20 to 35, and 46 to 53 and TPR repeats 1 to 6 and 10 to 14 were essential for viability.…”
Section: Sequence Analysis Of Tra1 and Trrapsupporting
confidence: 82%
See 1 more Smart Citation
“…A single deletion at the junction of the PI3K C-terminal lobe and FATC domain gave rise to viable yeast, whereas a complete deletion of the FATC domain was inviable, possibly due to poor protein stability, since this deletion resulted in a truncation in the C terminus (see below). This is consistent with a previous study suggesting that the FATC domain is important for integrity of complexes containing members of the PIKK protein family (36,41). We also found that Tra1 regions spanning HEAT repeats 8 and 9, 10 to 25, 20 to 35, and 46 to 53 and TPR repeats 1 to 6 and 10 to 14 were essential for viability.…”
Section: Sequence Analysis Of Tra1 and Trrapsupporting
confidence: 82%
“…The C terminus of PIKK proteins contains a FATC domain (FAT C-terminal) composed of one short and one long helix that are joined by a disulfide bond (20). However, one or both of these cysteines are missing in Tra1/TRRAP (36). Finally, the HEAT domain folds into a number of ␣-helical HEAT repeats that extend from the N terminus to the FAT domain, representing more than half the length of the protein.…”
Section: Sequence Analysis Of Tra1 and Trrapmentioning
confidence: 99%
“…S1A). This domain has been shown to play a very important role for the regulation of TOR and the other phosphoinositide-3 kinase-related kinase (PIKK) family members [8,[12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…S1B). The superpositions of the 1 H- 15 N-HSQC spectra of wild type and several mutant y1fatc proteins in the free form and with DMPC/DihepPC bicelles are shown in Fig. 3 (A-B untagged wild type and Y2463D/I2464D/W2466A, C-F Gb1-tagged y1fatc-L2459A, -Y2463A, -Y2463E/W2466E, -H2462R/Y2463D/I2464D/G2465S/W2466S/F2469D) and SI Fig.…”
Section: Mutation Of Up To 6 Residues Of Y1fatc Membrane Anchor Did Nmentioning
confidence: 99%
See 1 more Smart Citation